2009
DOI: 10.1128/jvi.00201-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ribavirin on the Mutation Rate and Spectrum of Hepatitis C Virus In Vivo

Abstract: Their extremely error-prone replication makes RNA viruses targets for lethal mutagenesis. In the case of hepatitis C virus (HCV), the standard treatment includes ribavirin, a base analog with an in vitro mutagenic effect, but the in vivo mode of action of ribavirin remains poorly understood. Here, we test the mutagenic effects of ribavirin plus interferon treatment in vivo using a new method to estimate mutation rates based on the analysis of nonsense mutations. We apply this methodology to a large HCV sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
132
5
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 43 publications
6
132
5
3
Order By: Relevance
“…Error catastrophe is defined as a loss of genetic fidelity during RNA virus replication that results in a lethal accumulation of errors. Ribavirin increases the level of genetic variation or mutation load in hantaviruses, polioviruses, and others in the presence of ribavirin in vitro, resulting in error catastrophe or lethal extinction once a specific level of mutation is achieved by the drug (18,(27)(28)(29)(30)34). Therefore, one might predict that coupled with normal within-host selection processes, ribavirin would be even more effective in causing error catastrophe or lethal extinction of the virus in vivo than in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Error catastrophe is defined as a loss of genetic fidelity during RNA virus replication that results in a lethal accumulation of errors. Ribavirin increases the level of genetic variation or mutation load in hantaviruses, polioviruses, and others in the presence of ribavirin in vitro, resulting in error catastrophe or lethal extinction once a specific level of mutation is achieved by the drug (18,(27)(28)(29)(30)34). Therefore, one might predict that coupled with normal within-host selection processes, ribavirin would be even more effective in causing error catastrophe or lethal extinction of the virus in vivo than in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed a lethal murine model of hantaviral disease with a prototypic HFRS virus, HTNV, to gain insight into viral replication and genetic variation over time with and without ribavirin treatment. Our research and that of others have shown that small molecules such as ribavirin increase the mutation load of the viral genome, which results in the extinction of the virus in vitro (18,(27)(28)(29)(30)34). Improving our understanding of how to drive a virus to extinction by increasing genetic variation by use of small antiviral molecules such as ribavirin (e.g., lethal mutagenesis) requires insight into how viruses evolve and adapt within different environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, this method provides an estimate of mutation rate per replication event (m/b/r) rather than by generation, as in the first method. Following Cuevas et al (2009), it is possible to calculate a mutation rate for the ith amplicon using the expression…”
Section: Virus and Plantsmentioning
confidence: 99%
“…HCV is classified into six major genetic groups, each further divided into more closely related subtypes, and within an infected individual the virus exists as a constantly evolving quasispecies (40). The genetic variability of HCV is owed to a high viral replication rate and an error-prone RNA-dependent polymerase (NS5B) with an estimated mutation rate of 10 Ϫ4 per nucleotide per generation (12).…”
mentioning
confidence: 99%